On Delay of the Delayed Choice Experiment - 孙君 孙永南 李传锋 郭光灿 (Chinese physics letters, 2015)
Following a suggestion by Wheeler, several delayed choice experiments have been performed. However, in those experiments one fact has always been ignored： that due to the fact that the single photon is nonlocal in time, the outcome will change if one changes the time to switch the experimental configuration within the photon＇s wavepaeket. This study obtains some insights into this aspect by proposing an experimental scheme based on the delayed choice experiment and giving some related analysis. The result shows a transitional behavior from a particle to a wave, leading to a conclusion that the measuring operator could be time dependent and be changed in a single measurement.